Leveraging Digital Platforms for Marketing in Indonesia: Strategies and Challenges - Ansir Launtu; Siti Nurhayati; Muh. Abduh Anwar; Klemens Mere; Loso Judijanto (Universitas Syiah Kuala and Collaboration Yayasan Yusda Edu Indonesia, 2026)
The digital landscape in Indonesia has undergone significant transformations, reshaping marketing strategies, presenting challenges, and unveiling new opportunities for businesses. This article conducts a comprehensive literature review spanning from 2019 to explore the dynamics of digital marketing transformation in Indonesia. The study investigates various strategies adopted by businesses to leverage digital platforms effectively, including social media marketing, influencer collaborations, search engine optimization (SEO), and content marketing. Moreover, it delves into the challenges encountered during the digital transformation process, such as technological limitations, privacy concerns, and the need for skilled digital marketing professionals. Furthermore, the article sheds light on the abundant opportunities emerging from Indonesia's digital evolution, such as access to a vast and diverse online audience, increased market reach, and enhanced customer engagement. By synthesizing recent scholarly works, industry reports, and empirical studies, this paper offers valuable insights into the current state of digital marketing in Indonesia. The findings contribute to the understanding of digital marketing strategies tailored to the Indonesian market context, while also highlighting areas for further research and strategic refinement. As Indonesia continues to embrace digitalization, understanding its unique challenges and opportunities becomes imperative for businesses aiming to thrive in the digital era.